FLAMING AS VERBAL CYBERBULLYING ON TIKTOK COMMENTS TOWARDS RACHEL ZEGLER AS SNOW WHITE - Simanjuntak, Juni Santa; Afandi, Fahri; Trifena, Atalya; Salim, Fahri; Putri, Dian Marisha (Ma Chung Press, 2025)
This study applied the Speech Act Theory by Austin and Searle to analyze verbal cyberbullying on TikTok comments toward Rachel Zegler, who took a role as Snow White and classified it into several categories and subcategories of illocutionary acts. This study utilised a descriptive qualitative approach to analyze linguistic forms of verbal cyberbullying in the data. The data collected through documentation and observation of several contents related to Rachel Zegler. The analysis result shows that the domination of expressive (insulting) acts occurred in the verbal cyberbullying data collected, with a total of 25 utterances (50%). Assertive (stating) acts became the second most dominant with a total of 7 utterances (14%), followed by assertive (asserting) with 4 utterances (8%), assertive (complaining) with 3 utterances (6%) and assertive (criticizing) with 2 utterances (4%). While the least dominant acts were assertive (predicting) and (comparing), directive (requesting/demanding) and commissive (committing), with each having a single utterance (2%). This study reveals that most people used expressive (insulting) acts in doing flaming as a form of verbal cyberbullying on TikTok. This research contributes to raising awareness among digital media users about the importance of the use of appropriate language in fostering constructive criticism and promoting healthier online interactions.